2014
DOI: 10.2190/ns.23.4.c
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Safety and Health Improvements through a Labor/Management Training and Collaboration

Abstract: Seven hundred thirty-nine workers at Merck's Stonewall plant in Elkton, Virginia, have a safer and healthier workplace because four of them were enthusiastic about health and safety training they received from the union's training center in Cincinnati, Ohio. What emerged was not only that all 739 plant employees received OSHA 10-hour General Industry training, but that it was delivered by “OSHA-authorized” members of the International Chemical Workers Union Council who worked at the plant. Merck created a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
(10 reference statements)
1
14
0
Order By: Relevance
“…This finding is consistent with previous work documenting the importance of worker engagement in health and safety (e.g., Smitha et al, ; Mahan et al, ). In addition to the safety committee, safety leadership encompasses numerous factors associated with lower injury rates such as management commitment to safety [Simonds and Shafai‐Sahrai, ; Smith et al, ; Habeck et al, ; Gilkey et al, ], designating person(s) responsible for safety [Shannon et al, ], incident investigation and recordkeeping [Simonds and Shafai‐Sahrai, ; Smith et al, ], and effective enforcement of safety policies [Bull, ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous work documenting the importance of worker engagement in health and safety (e.g., Smitha et al, ; Mahan et al, ). In addition to the safety committee, safety leadership encompasses numerous factors associated with lower injury rates such as management commitment to safety [Simonds and Shafai‐Sahrai, ; Smith et al, ; Habeck et al, ; Gilkey et al, ], designating person(s) responsible for safety [Shannon et al, ], incident investigation and recordkeeping [Simonds and Shafai‐Sahrai, ; Smith et al, ], and effective enforcement of safety policies [Bull, ].…”
Section: Discussionsupporting
confidence: 93%
“…However, incentive programs focusing on providing awards to employees solely for PPE use may only improve the employees' safety performance in the short term as they are unsustainable. On the other hand, incentive programs that promote safety awareness and employee participation in safety-related activities have been proven to be most effective [ 18 ]. Punishing noncompliance with PPE use protocol was another example of the desired safety climate of the workplace mentioned during FGDs.…”
Section: Discussionmentioning
confidence: 99%
“…Two other ICWUC studies reported success in systematically addressing worksite hazards after joint labor management programs trained the entire workforce in OSHA classes assisted by site trainers (Mahan et al, 2014 andMahan et al, 2018). This paper moves a step beyond to explore increased learning and activism from the continuing presence of a group of worker trainers on the shop floor, building an increasing infrastructure for making safety and health integral to daily activities.…”
Section: Literature Reviewmentioning
confidence: 93%